Multiply 3 and 2. You get 6.
What factors of 6 add up to 5? You get 3 and 2.
Insert these into the equation in place of 5x.
3x^2 + 3x + 2x + 2
Factor by grouping
= 3x(x+1) + 2(x+1)
= (3x+2)(x+1)
(3x+2)(x+1) = 0
Set each factor equal to zero.
3x+2 = 0 or x+1 = 0
x = -2/3 or x = -1
2007-05-31 06:23:26
·
answer #1
·
answered by MsMath 7
·
3⤊
1⤋
3x² + 5x + 2 = 0
The middle term is + 5x
Find the sum of the middle term
Multiply the first term 3 times the last term 2 equals 6 and factor
factors of 6
1 x 6
2 x 3. . . .<=. .Use these factors
+ 3 and + 2 satisfy the sum of the middle term
Insert + 3x and + 2x into the equation
3x² + 5x + 2 = 0
Gropup factor
3x² + 3x + 2x + 2 = 0
3x(x + 1) + 2(x + 1) = 0
(3x + 2)(x + 1) = 0
- - - - - - - -
Roots
3x + 2 = 0
3x + 2 - 2 = 0 - 2
3x = - 2
3x / 3 = - 2 / 3
x = - 2/3
- - - - - - - -
Roots
x + 1 = 0
x + 1 - 1 = 0 - 1
x = - 1
- - - - - - - - s-
2007-05-31 15:34:07
·
answer #2
·
answered by SAMUEL D 7
·
0⤊
0⤋
First, let's look at the 3 in front of the x^2. The only way to factor a 3 is 3*1 (or -3 * -1, but we can ignore that for the first term), so you know any factored solution must start with:
(3x ......... ) * (x ......... )
Next, look at the 2.
The only ways to factor a 2 are 2*1 and -2 * -1.
This leaves us with four possibilities:
(3x + 2)*(x + 1)
(3x + 1)*(x+2)
(3x - 2)*(x - 1)
(3x - 1)*(x - 2)
The last two possibilities can be thrown out, since they would lead to a negative coefficient for the middle term, and that coefficient needs to be 5.
Next, you FOIL out the two possibilities you have left, and see if either one works.
(3x + 2)*(x + 1) = 3x^2 + 5x + 2
(3x + 1)*(x + 2) = 3x^2 + 7x + 2
Looks like the first option is a winner!
2007-05-31 13:29:05
·
answer #3
·
answered by Bramblyspam 7
·
0⤊
1⤋
First: multiply the 1st & 3rd term to get 6. find two numbers that give you 6 when multiplied & 5 (2nd term) when added/subtracted. the numbers are (2 & 3). rewrite the expression with the new middle terms.
3x^2 + 2x +3x + 2 = 0
Sec: group "like" terms & factor both sets of parenthesis.
(3x^2 + 3x) + (2x + 2) = 0
3x(x + 1) + 2(x + 1) = 0
(x + 1)(3x + 2) = 0
Third: set both parenthesis to "0" & solve the "x" variables.
a. x+1 = 0
subtract 1 from both sides - when you move a term to the opposite side, always use the opposite sign.
x+1-1 = 0-1
x = -1
b. 3x+2 = 0
subtract 2 from both sides.
3x+2-2 = 0-2
3x = -2 (divide both sides by 3).
3x/3 = -2/3
x = -2/3
Solutions: -1 and -2/3
P.S. We solve the "x" variables because, the problem is an equation set to "0"
2007-05-31 15:30:04
·
answer #4
·
answered by ♪♥Annie♥♪ 6
·
0⤊
0⤋
(3x + 2)(x + 1)
I look at it this way:
The first term I look at is 3x^2. 3 happens to be prime, so you know that the first terms in the solution are some combination of 3x and 1x. (It also could be -3x and -x....)
Then I look at the last term of the polynomial: the 2. 2 is also prime, so the solution is a combination of 2 and 1 or -2 and -1.
To get the final solution, you have to solve for that 5x.
3x(a) + x(b) = 5x where a, b are either (-)1 or (-)2 (from the factors of the last term, 2.)
Since 3x(1) + x(2) = 5x, we get the final solution that the 3x and the 1 are in different factors.
(3x + 2)(x +1)
2007-05-31 13:42:55
·
answer #5
·
answered by milpool2005 2
·
0⤊
1⤋
The factors of 2 are 1,2...
You know you need a 3x^2 as the first term in the polynomial.
(3x + )( x + )
Now you need the middle term in the poly to add to 5 so you need to use the 2 to multiply with the x and not the 3x.
(3x + 2)(x + 1)
Test the result using FOIL (First outer inner last)
3x*x + 3x*1 + 2*x + 2*1 =
3x^2 + 3x + 2x + 2 =
3x^2 + 5x + 2 (check)
Hope this helps.
2007-05-31 13:27:38
·
answer #6
·
answered by Anonymous
·
0⤊
1⤋
3x^2 + 5x +2=0
=(3x + ?)(x + ?) = 0
Since ? times ? = 2 one ? 2 and the other =1.
So = (3x +2)(x+1) = 0
2007-05-31 13:34:05
·
answer #7
·
answered by ironduke8159 7
·
0⤊
1⤋
( 3 x +2 )(x+1)
2007-05-31 13:23:25
·
answer #8
·
answered by muhamed a 4
·
1⤊
3⤋
3x^2+5x+2=3x^2+3x+2x+2
3x(x+1)+2(x+1)
=(x+1)(3x+2)answer
2007-05-31 13:25:39
·
answer #9
·
answered by Anonymous
·
0⤊
1⤋